Current Understanding of the Red Blood Cell Diseases - Yeh, Victor; Ji, MD, PhD, Peng (North American Journal of Medicine and Science, 2009)
The human red blood cell is produced continuously from hematopoietic stem cells in the bone marrow. These hematopoietic stem cells can differentiate into red blood cell precursors, which continuously produce hemoglobin until it accounts for roughly 90% of the dry cell weight. The red blood cell precursors then undergo enucleation, a process in which the nucleus of the precursor cell is squeezed out to generate a mature red blood cell.1 The mature red blood cell takes the rather unique shape of a biconcave disk, which is maintained by structure proteins in the cell membrane. The life span of a mature erythroblast is roughly 120 days in humans. A variety of red blood cell diseases are known, such as anemia, sickle cell diseases, malaria, hemolysis and polycythemias. Diseases involving red blood cells are generally due to three factors: genetic deficiency, poor nutrition or parasitic infection. In the past years, progress in genetic and molecular research tools has allowed for a deeper understanding of red blood cell diseases. In this paper, we’ll provide a review of advances in understanding and treatment of the most common red blood cell diseases: namely Malaria, Sickle Cell Disease, and Iron Deficiency Anemia.